Modeling of plastic zones before the crack's peak of given structure constructional materials - Матченко, Т.І.; Тертична, В.А. (Proceedings of National Aviation University (archive), 2005)
The basic kinds of deformation in plastic zones near top of a crack are determined.Zones are determined, in which the sliding in crystals ,between grains sliding and plastic deformation of a continuous body is typical.